2006
DOI: 10.1111/j.1365-2044.2006.04584.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and heart rate changes during intubation: a comparison of direct laryngoscopy and a fibreoptic method

Abstract: SummaryBlood pressure and heart rate changes during nasotracheal intubation under general anaesthesia were studied in 100 patients who were randomly allocated to fibreoptic bronchoscope or direct laryngoscopy intubation. Noninvasive blood pressure and heart rate were recorded before and immediately after anaesthesia induction, at anaesthesia intubation and every minute thereafter for 5 min. Nasotracheal intubation was accompanied by significant increases in blood pressure and heart rate compared to baseline va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 19 publications
(22 reference statements)
1
12
0
3
Order By: Relevance
“…Maximum increase in heart rate and mean arterial blood pressure was at the end of endotracheal intubation (Table 2). Our results are in consistence with the results of Singh et al [4], Finfer et al [5] and Xue et al [6] which showed significant rise in heart rate and blood pressure during and after nasotracheal intubation.…”
Section: Discussionsupporting
confidence: 93%
“…Maximum increase in heart rate and mean arterial blood pressure was at the end of endotracheal intubation (Table 2). Our results are in consistence with the results of Singh et al [4], Finfer et al [5] and Xue et al [6] which showed significant rise in heart rate and blood pressure during and after nasotracheal intubation.…”
Section: Discussionsupporting
confidence: 93%
“…(14) When Xue et al compared nasal FOI with direct laryngoscopy for asleep nasal tracheal intubation, they found that nasal FOI was associated with significantly higher mean systolic blood pressure (126.9 ± 21.6 mmHg vs. 108.8 ± 11.1 mmHg, respectively) and heart rate (100.5 ± 16.4 bpm vs. 87.6 ± 17.9 bpm, respectively) compared with baseline values (similar for both groups). (15) The higher systolic blood pressure and heart rate occurred despite avoidance of direct stimulation of the tongue base during nasal FOI, thereby minimising gagging and its associated pressor response. The patients had no airway topicalisation.…”
Section: Airway Complicationsmentioning
confidence: 99%
“…The cardiovascular responses during FOI were attributed to prolonged intubation times (the resulting hypercarbia causes a rise in blood pressure and heart rate, but the authors considered this a minor contributory factor), FOI stimulation of the oropharyngeal structures, and jaw thrust. (15)…”
Section: Airway Complicationsmentioning
confidence: 99%
“…Airway manipulations such as laryngoscopy and naso or oropharyngeal intubation during general anesthesia are considered noxious stimuli that result in undesirable responses as tachycardia, hypertension, arrhythmia, pulmonary hypertension, and increased airway reactivity. Laryngoscopy causes at least 20 mmHg increase in systolic blood pressure [1]. Intracranial pressure increases at least 5 mmHg with simple tracheal suction [2].…”
Section: Introductionmentioning
confidence: 99%